Determination of Ti, Zr, Nb, V, W and Mo in seawater by a new online-preconcentration method and subsequent ICP–MS analysis - Poehle, Sandra; Schmidt, Katja; Koschinsky, Andrea (Deep-sea research. Part I, Oceanographic research papers, 2015)
We present a new method for the determination of Ti, Zr, Nb, V, W and Mo in seawater by adapting the online-preconcentration procedure with the system SeaFAST and subsequent analysis by ICP–MS to these metals. The trace elements Ti, Zr, Nb and W are present in seawater in ultratrace concentrations in the range of pmolkg−1, whereas Mo and V, which are biologically essential elements, are present in the concentration range of nmolkg−1. The online-preconcentration system we used consists of an autosampler, a sample loop, a preconcentration column and two valves controlling the sample loop and the preconcentration processes. The pre-packed preconcentration column contains a chelating resin with two functional groups, ethylenediamine triacetic acid (EDTriA) and iminodiacetic acid (IDA), immobilized on a polymer backbone. The preconcentration process was optimized for loading the sample and subsequent rinsing to remove residues of seawater matrix prior to elution with the optimized elution acid (0.5M HNO3–0.002M HF). We used acidified North Sea seawater (0.02M HCl–0.002M HF) for the method development. Samples and calibration standards were loaded onto the preconcentration column and after elution directly transferred to the quadrupole ICP–MS and measured immediately. Best results were achieved with matrix-matched calibration standards (0.6M NaCl–0.02M HCl–0.002M HF) simulating acidified seawater samples. Titanium, Zr, Nb and W are measured simultaneously in one run, whereas V and Mo are determined simultaneously in a separate run. Low procedure blanks were calculated for Ti, Zr, Nb, W (635, 14.5, 1.35, 10.2pmolkg−1) and for V and Mo, 9.79 and 5.61nmolkg−1, respectively. Very good spike recoveries achieved with spiked North Sea water demonstrate the applicability for all six elements. Analysis of the seawater standard NASS-6 gave recoveries of 97–99% (0.9–2.2% standard deviation, SD) for Mo and V. We also provide Zr, Nb and W data for this reference standard. The applicability of the on-line preconcentration method was demonstrated for samples collected during a GEOTRACES cruise in the Atlantic. Due to the low limit of quantification, LOQ, and SD, this method enables the determination of ultratrace concentration levels for Ti, Zr, Nb and W as well as the detection of small variations in concentration for all six elements. The required sample volume of only 50mL, the fast determination within 1h for all elements and the principle of a closed system are a clear advantage of the analytical procedure compared to many other methods and facilitates sample logistics for the determination of Ti, Zr, Nb, V, W and Mo in seawater. [Display omitted] •Online-preconcentration method for Ti, Zr, Nb, V, Mo and W in seawater.•Detection of ultratrace concentrations for Ti, Zr, Nb and W in seawater.•Low standard deviation of the method enables detection of small variations Mo and V.•Spikes for Ti, Zr, Nb, V, Mo and W were recovered quantitatively in North Sea water.•Quantitative recovery of V and Mo in seawater reference standard NASS-6.